Proceeding of the 12th Joint workshop on electron cyclotron emission and electron cyclotron heating : (World Scientific, 2003)
The 12th Joint Workshop on Electron Cyclotron Emission and Electron Cyclotron Resonance Heating (EC-12) was held in Aix-en-Provence (France) from May 13 to 16, 2002. This workshop was concerned with the interaction of electromagnetic waves and hot plasmas, a subject of great importance in the framework of research on controlled thermonuclear fusion. Using as a fuel a mixture of deuterium and tritium, which can be extracted from sea water, this is a very promising way to develop an intrinsically safe reactor. The workshop gathered approximately one hundred specialists in the production, use and theory of millimetre waves for heating and diagnostics of fusion plasmas.